Strategi Marketing Politik Anies Baswedan Dan Muhaimin Iskandar (Amin) Pada Pemilu Tahun 2024 Melalui Youtube - Sumardi; Nurmiati; Baharuddin; Jamaluddin (STISIP Widyapuri Mandiri Sukabumi, 2024)
This research aims to determine the political marketing strategy of Anies Baswedan and Muhaimin Iskandar (AMIN) as Presidential and Vice Presidential Candidates in the 2024 Presidential Election, focusing on the YouTube platform through the 4P marketing-mix approach by Niffenegger (1989). The research method used is descriptive qualitative. The research results show that the AMIN pair has strong support from a coalition of parties and non-parliamentary parties, and has a positive track record. The promotional strategy via YouTube has proven to be effective with personal channels that have a significant number of subscribers and the use of popular hashtags such as #aminajadulu. Despite limited campaign funds, AMIN succeeded in optimizing self-help support and establishing cooperation with prospective legislative members. In addition, AMIN's campaign locations and targets are in accordance with the characteristics of voters in the 2024 presidential election, especially the Millennial and Gen Z generations. Through creative portals such as https://gagasankita .id/home and the Desak Anies and Slepet Imin programs, AMIN has succeeded in engaging with various segments of society. This research provides an in-depth understanding of the effectiveness of political marketing strategies via the YouTube platform, describes political support, and highlights success in accessing the Millennial and Gen Z generations.